Pemahaman Mahasiswa tentang Konsep Fisika dalam Al-Qur’an: Analisis Fenomena Alam pada Ayat-Ayat Kauniyah - Silvianty, Alvionita (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2025)
Science and religion are often regarded as distinct domains, yet they can complement each other in understanding the universe. This study aims to describe students’ understanding of physical science concepts in the kauniyah verses of the Qur’an. A descriptive method with a qualitative approach was used. A total of ten physics education students were selected as participants using a purposive sampling technique. Data were collected through semi-structured interviews and analyzed thematically. The findings reveal that most students could relate kauniyah verses to physical concepts such as Earth's rotation, time relativity, tectonic plates movement, and light. However, variations in understanding were found, with some students emphasizing religious aspects without deep scientific reasoning. These results highlight the importance of integrating science and Islamic values in learning to strengthen students’ conceptual understanding.Keywords: kauniyah verses, physical phenomena, Islam-science integration